Katalogų sistemos pertvarkymas tarybinės bibliotekininkystės pagrindais Vilniaus universiteto bibliotekoje (1948–1953) - Kastanauskaitė, Danutė (Knygotyra, 1973)
In 1940 Vilnius University library inherited the catalogue system that diversely and inadequately represented the stock of the library. The books were catalogued on the basis of the Polish-Prussian regulations known for their scatiness. The cards of different size prevailed in the catalogues. The proper get-up was missing. The catalogues of some departmental libraries had no contact with the main library.The general development of science and education at Vilnius University, the increasing demands of the readers, the growing stock in the library and the change in its composition and location determined the formation of entirely new system.Already in 1940–1941 most attention was devoted to the cataloguing of Soviet literature, to the methodology of more dignified cataloguing system, to the revision of departmental libraries and providing with the personnel.The first undertakings of the Soviet years were put inte life in the years 1948–1953. The catalogues of the library were classified according to their purpose, the type of the book, the language, the volume of the stock. The scheme of the main alphabetic and subject catalogues was developed. The catalogues were cleared from outdated literature and recatalogued. In cataloguing the books use was made of the Soviet Catalogue regulations and internationally used cards adopted. Following the example of the Soviet libraries the methodology of the subject catalogue classification was put into practice.Due to the great efforts Levas Vladimirovas, Director of the library since 1948, succeeded in organizing the catalogue reform. Thanks to this devotion the book−managing department has been reorganized, the personnel provided, the whole process of methodology work rationalized.All these measures enabled the new catalogues system not only to make the stock of the library accessible, but also propogate it from the marxist-leninist viewpoint of science.The article draws a conclusion that it was the catalogue differentiation instituted in 1948–1953, the organization of the departmental catalogues and the staff provision that played the most important role in the development of the present-day catalogue system.